Identification of tephra horizons in a glacier on the Ushkovsky volcano (Kamchatka) - N. V. Gorbach; T. M. Philosofova; V. N. Mikhalenko (Лëд и снег, 2024)
Identification of tephra and its allocation (association) with known eruptive events allows obtainng chronostratigraphic markers, on the basis of which an age scale for dating glacial strata can be developed. To determine the sources of ash in the ice core obtained in 2022 during drilling of glacier in the crater of the Ushkovsky volcano in Kamchatka, the chemical composition of volcanic glass in individual ash particles was analyzed. The accuracy of determination of the volcanic glass composition was verified by analyzing of international standard samples of volcanic and synthetic glass. Based on a comparison of the data we obtained with published data on the composition of tephra glasses from the present-day eruptions in Kamchatka, we determined affiliation of each tephra horizon to specific volcano-source. We have found that the main source of tephra in the ice core of the Ushkovsky Glacier is the Kliuchevskoi volcano, which is the closest and the most productive one among the Kamchatka volcanoes. Ash particles from Bezymyannyi volcano were identified in two horizons. A mixed population of particles was found in one of the horizons, including the ash particles from volcanoes Kizimen, Kliuchevskoi and Bezymyannyi. Analysis of published data on the chronology and distribution of ash plumes from known eruptive events made it possible to confidently correlate the tephra horizon at a depth of 762–777 cm with the initial phase of the eruption of the Kizimen volcano in late 2010–early 2011. Ash from the uppermost tephra buried in the glacier at depths of 89–94 cm belongs to the Bezymyannyi volcano eruption, which the most likely occurred in October 2020. Single particles with rhyolitic composition of glass in the sample from the depth of 348–354 cm may belong to the eruption of the Shiveluch volcano in December 2018. The results of our work can be used on further studying of the ice core from the Ushkovsky volcano, in particular for comparison and correlation with the chronostratigraphic data obtained by glacio-chemical and isotope methods.